Profitability, Input Elasticities and Economic Efficiency of Poultry Production among Youth Farmers in Osun State, Nigeria - Oladeebo, J.O.; Ambe-Lamidi, A.I. (International Journal of Poultry Science, 2007)
The aim of the study was to determine the profitability, returns to scale and economic efficiency of poultry production by youth farmers in Osun State, Nigeria. Primary data were obtained from 62 representative farmers drawn from the study area using simple random technique. Data were analyzed by the use of descriptive statistics, multiple regression and costs and returns analysis. The results showed that majority of the poultry farmers were in the age range of between 20 and 29 years and were highly educated. The results revealed that youth poultry farmers had positive decreasing returns to scale (RTS = 0.76) in poultry production which indicated that poultry production was in the rational stage of production (Stage II). The results obtained further revealed that although youth poultry farmers were not fully economically efficient in the use of resources, poultry production was profitable among youth poultry farmers. The study concluded by making suggestions which could improve the profitability of poultry production among the youth in the study area and in Nigeria as a whole.